1993
DOI: 10.1037/0022-006x.61.6.1046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a sexual assault prevention program.

Abstract: The purpose of this investigation was to empirically evaluate a sexual assault prevention program. Of the 360 female college students who participated in the investigation, 181 students were in the treatment group and 165 students were in the control group. Although the program was not effective in decreasing the incidence of sexual assault for women with a sexual assault history, it was effective in decreasing the incidence of sexual assault for women without a sexual assault history. The program also led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
225
2
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(236 citation statements)
references
References 12 publications
5
225
2
4
Order By: Relevance
“…All subjects were then required to return at the end of the academic quarter and complete a series of outcome measures. Hanson and Gidycz (1993) were able to demonstrate a statistically significant decrease in the rates of sexual assault over a 9-week period among college women who did not report a prior history of sexual victimization. They also found that the intervention was effective in increasing knowledge regarding sexual assault and altering dating behaviors that have been shown to be highly correlated with rape.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…All subjects were then required to return at the end of the academic quarter and complete a series of outcome measures. Hanson and Gidycz (1993) were able to demonstrate a statistically significant decrease in the rates of sexual assault over a 9-week period among college women who did not report a prior history of sexual victimization. They also found that the intervention was effective in increasing knowledge regarding sexual assault and altering dating behaviors that have been shown to be highly correlated with rape.…”
mentioning
confidence: 82%
“…The program developed by Hanson and Gidycz (1993) has been the most successful to date. Despite the "clinical lore" which often suggests that selfdefense tactics are the most effective strategies for women to learn, no prospective studies, without self-selected samples, have been conducted to evaluate the efficacy of such interventions.…”
Section: Self-defense Approaches To Primary Prevention With Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Hanson and Gidycz (1993) found that a sexual assault prevention program reduced the incidence of sexual assault among women who had not been previously victimized. The program was not effective, however, in reducing the incidence of sexual assault among women who had been previously victimized.…”
Section: Evaluation Of Programs Targeting Sexual Victimizationmentioning
confidence: 99%
“…Similarly, in two separate studies, women who had experienced sexual victimization were assigned to a control or a treatment condition. Both conditions consisted of a single session providing information regarding the prevalence of sexual assault on college campuses, reviewing situational risk factors for sexual assault, and discussing protective behaviors (Breitenbecher & Gidycz, 1998;Hanson & Gidycz, 1993). Breitenbecher and Gidycz (1998) also provided participants with information on the role of psychological effects of an initial victimization experience in putting women at increased risk for revictimization.…”
Section: Evaluation Of Programs Targeting Sexual Victimizationmentioning
confidence: 99%